2013
DOI: 10.4049/jimmunol.1300081
|View full text |Cite
|
Sign up to set email alerts
|

HLA-F and MHC Class I Open Conformers Are Ligands for NK Cell Ig-like Receptors

Abstract: Killer Immunoglobulin-like receptors (KIR) are innate immune receptors expressed by NK and T cells classically associated with the detection of missing-self through loss of their respective MHC ligand. Some KIR specificities for allelic classical class I MHC (MHC-I) have been described, while other KIR receptor-ligand relationships, including those associated with non-classical MHC-I, have yet to be clearly defined. We report here that KIR3DL2 and KIR2DS4 and the non-classical antigen HLA-F, expressed as a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 49 publications
7
115
3
1
Order By: Relevance
“…It is tempting to speculate that functionally analogous systems exist in mice and humans, whereby the CD94-NKG2 receptors exclusively bind HLA-E/Qa-1 b , whereas Ly49/KIR bind a more diverse but structurally related group of molecules extending into non-classical MHC ligands. It is interesting to note recent evidence suggests that the MHC-Ib HLA-F is a ligand for KIR3DL2 and KIR2DS4 (38). It is also possible that unlike MHC-Ia, where the need to present diverse peptide repertoires for T cell recognition has driven the acquisition of polymorphism, the capacity of a number of MHC-Ib to interact with immunoreceptors such as those of the Ly49 family may have served to limit their genetic diversification.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that functionally analogous systems exist in mice and humans, whereby the CD94-NKG2 receptors exclusively bind HLA-E/Qa-1 b , whereas Ly49/KIR bind a more diverse but structurally related group of molecules extending into non-classical MHC ligands. It is interesting to note recent evidence suggests that the MHC-Ib HLA-F is a ligand for KIR3DL2 and KIR2DS4 (38). It is also possible that unlike MHC-Ia, where the need to present diverse peptide repertoires for T cell recognition has driven the acquisition of polymorphism, the capacity of a number of MHC-Ib to interact with immunoreceptors such as those of the Ly49 family may have served to limit their genetic diversification.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, mAbs to a conformed heavy chain epitope (W6/32) and to β 2 m (NAMB-1) coimmunoprecipitated β 2 m and HLA-E, respectively, particularly from 221.AEH cells (lanes 2, 3, 8, 9, 16, 17, 22, and 23). In contrast, mAbs to HLA-E (MEM-E/02, 3D12, and DT9) immunoprecipitated HLA-E heavy chains in comparable amounts (lanes 4-6 and 10-12), but only mAb 3D12 coimmunoprecipitated β 2 m in very low amounts and exclusively from 221.AEH cells (lanes [18][19][20][24][25][26]. Likewise, mAbs MEM-E/07 and MEM-E/08 did not detectably coimmunoprecipitate β 2 m (not shown, and see ref.…”
Section: Different Mabs Bind Different Hla-e Foldsmentioning
confidence: 99%
“…At least two groups have demonstrated that "open conformers" of classical class I heavy chains and HLA-F are sufficiently folded to engage innate immune receptors including LILRB, LILRA1, LILRA3 [24], KIR2DL2, and KIR2DS4 [25]. In this light, CD94:NKG2A blockade by mAb 3D12 [26] raises the issue of whether NK cells might also be regulated by the free HLA-E heavy chains present in the 3D12 molecular pool.…”
Section: Hla-e: Folding and Functionmentioning
confidence: 99%
“…HLA-I molecules have been implicated in interactions with other receptors both in trans and in cis, and the full-length HLA-I H chain can form a homodimer similar to HLA-A11svE4. Geraghty and colleagues (17)(18)(19)(20) showed that HLA-F and MHC-I OCs are devoid of b2m, but cooperate in a MHC-I Ag-crosspresentation pathway, although they also observed HLA-F and MHC-I OCs without Ags. Interestingly, they also proved that the OCs of HLA-F and MHC-I are ligands of KIR.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors showed that HLA-F and MHC-I OCs operate together in activated lymphocytes and monocytes in an Ag cross-presentation pathway, which suggested that complexes with two MHC-I H chains have the ability to present Ags (18). Furthermore, research has also shown that the OCs of HLA-F and MHC-I bind to KIR3DL2 to inhibit NK activation (19,20). Taken together, these results indicated that the OCs are functional in the immune system.…”
mentioning
confidence: 99%